Upaya Mengurangi Pengangguran Melalui Usaha Mikro Kecil dan Menengah (UMKM) di Provinsi Banten - Hartika, Nely; Jumiati, Ipah Ema; Damarwulan, Liza Mumtazah; Sudrajat, Agung; Widyawati, Widyawati; Rudiansyah, Rudiansyah (Program Studi Administrasi Negara Universitas Serang Raya, 2023)
This research background is that there is an increase in the unemployment rate in Banten Province, and available labor resources in the labor market in Banten Province are growing every year. But on the other hand, due to the increase in the unemployment rate every year and the increase in the number of workers, the existing workforce is not being absorbed properly. The purpose of this research is to find out how efforts to deal with unemployment through efforts to reduce unemployment through micro, small and medium enterprises (UMKM) in Banten Province. In this study, researchers used qualitative research methods. Small and medium enterprises in Banten Province absorb 235,022 workers, namely the food industry with 91,476 workers. followed by the garment industry with 34,508 people, and the wood and cork industry excluding furniture with 3,056 people. MSMEs have made a major contribution to economic growth and have had a positive impact on people's welfare, especially those in Banten Province